Моніторинг фізичних рухів - Гаденко, В. Ю. (ХНУРЕ, 2024)
Nowadays, where health and physical well-being are becoming increasingly important, regular exercise is considered a key element in maintaining overall well-being. However, improper exercise techniques can lead to a decrease in their effectiveness and, even worse, a risk of injury. This is especially true for beginners, who often face difficulties in mastering the correct techniques without the direct supervision of a trainer or specialist. The use of video monitoring can help many people monitor their activity and exercise technique, provide useful feedback, and ultimately increase physical activity levels and overall public health.
Keywords: фізичні рухи